2022
DOI: 10.3389/fpls.2022.817356
|View full text |Cite|
|
Sign up to set email alerts
|

Polymerase II–Associated Factor 1 Complex-Regulated FLOWERING LOCUS C-Clade Genes Repress Flowering in Response to Chilling

Abstract: RNA polymerase II–associated factor 1 complex (PAF1C) regulates the transition from the vegetative to the reproductive phase primarily by modulating the expression of FLOWERING LOCUS C (FLC) and FLOWERING LOCUS M [FLM, also known as MADS AFFECTING FLOWERING1 (MAF1)] at standard growth temperatures. However, the role of PAF1C in the regulation of flowering time at chilling temperatures (i.e., cold temperatures that are above freezing) and whether PAF1C affects other FLC-clade genes (MAF2–MAF5) remains unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…With elf7-3 plants, the presence of NaCl resulted in distinctly lower transcriptional response, indicating that ELF7 plays an important role in the response to elevated NaCl concentrations. In agreement with our findings, a recent study concluded that Col-0 and cdc73 Arabidopsis plants grown at 23°C have a similar transcriptome, and that elf7 and vip3/4/5/6 share a large number of DEGs ( Nasim et al., 2022 ). In yeast as well as in mammals, PAF1C subunit mutants are also associated with a range of phenotypes suggesting (partial) subunit specificity ( Betz et al., 2002 ; Akanuma et al., 2007 ; Chu et al., 2007 ; Cheung et al., 2008 ; Wang et al., 2008 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…With elf7-3 plants, the presence of NaCl resulted in distinctly lower transcriptional response, indicating that ELF7 plays an important role in the response to elevated NaCl concentrations. In agreement with our findings, a recent study concluded that Col-0 and cdc73 Arabidopsis plants grown at 23°C have a similar transcriptome, and that elf7 and vip3/4/5/6 share a large number of DEGs ( Nasim et al., 2022 ). In yeast as well as in mammals, PAF1C subunit mutants are also associated with a range of phenotypes suggesting (partial) subunit specificity ( Betz et al., 2002 ; Akanuma et al., 2007 ; Chu et al., 2007 ; Cheung et al., 2008 ; Wang et al., 2008 ).…”
Section: Discussionsupporting
confidence: 93%
“…Elongator, SPT4-SPT5, TFIIS) exhibit differential expression of only subsets of genes ( Nelissen et al., 2005 ; Grasser et al., 2009 ; Dürr et al., 2014 ). Likewise, relative to wild type under normal growth conditions, based on microarray hybridization experiments ( Park et al., 2010 ) or RNA-seq of total mRNA ( Nasim et al., 2022 ), several hundreds of DEGs were observed for mutants deficient in PAF1C subunits, except for cdc73 , whose transcriptome was similar to that of wildtype. Consistently, using high-throughput sequencing of nuclear mRNAs, we identified 12 and 722 DEGs in cdc73-2 and elf7-3 , respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The roles of PAF1C in transcription regulation have been well‐studied (Moniaux et al , 2006; Jaehning, 2010; Antosz et al , 2017; Vos et al , 2018; Nasim et al , 2022). Here we found that PAF1C plays a critical role in DSB repair.…”
Section: Discussionmentioning
confidence: 99%